IMPLEMENTASI DIGITALISASI SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA SEKOLAH DASAR - Abdul Latip; TARYUDI, TARYUDI; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of conventional academic supervision in elementary schools often faces constraints such as time constraints, limited documentation space, and slow feedback. This results in a suboptimal evaluation process and hinders the acceleration of improving the quality of teacher teaching in the classroom. This study aims to analyze and describe the implementation of digitalized supervision by principals and its impact on improving teacher performance at the elementary school level. This study used a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with principals and teachers, direct observation of the digital-based supervision process, and documentation study related to performance assessment results. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The study shows that implementing digitalized supervision through a dedicated  application or school management platform can improve the efficiency, transparency, and objectivity of the assessment process. Principals can provide instant (real-time) feedback, allowing teachers to quickly access evaluation results for teaching improvement. The use of this digital instrument has been proven to significantly improve teacher discipline, motivation, and pedagogical competence, ultimately positively impacting the quality of learning. However, the success of this system still requires support in improving teachers' digital competencies and providing adequate infrastructure.